USE OF PUBLIC ROADS FOR WEDDINGS IN THE PERSPECTIVE OF ISLAMIC LAW AND POSITIVE LAW - Rizal, Sofian Syaiful (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Public roads are shared facilities passed by the community to support their mobility. Islamic teachings stipulate that public roads are a basic human right that no one may hinder. However, some people have taken advantage of public roads for the benefit of weddings and other private events, thereby disrupting and hindering community activities. This paper aims to examine the use of public roads in weddings from the perspective of Islamic law and positive law by focusing on two questions: First, what is the view of Islamic law on the use of public roads for weddings in society? Second, what are the regulations for using public roads for people holding wedding events in the community based on the Police Chief Regulation No. 10 of 2012 concerning road use other than for traffic activities? This type of research is library research with a qualitative approach. Data collection was carried out by reading news, books and articles related to the research problem and then analyzed using the deductive method. The results of the study show that weddings are included as road use for personal gain. The use of roads that are private, among others, for weddings, funerals, or other activities. Roads that can be used for private purposes are regency roads, city roads and village roads. If the use of the road results in road closure, a road use permit must be issued by the Indonesian National Police (“Polri”). Based on Article 17 of the Police Headquarters Number 10 of 2012, which contains how to obtain a road use permit.